L’environnement autour des écoles a-t-il un impact sur le risque routier impliquant des enfants piétons à Montréal ? - Marie-Soleil Cloutier; Philippe Apparicio (Territoire en Mouvement)
Despite the great amount of prevention, child pedestrian victims in school context in Montreal remained almost constant from 1999 to 2003. On the other hand, the elementary public school environment has been barely taken into account in research on factors affecting the risk of accident of these vulnerable users. The objective of this paper is to explore the influence of different socio-economic and environmental variables on child pedestrian risk through the modeling of the surroundings of the school. The proposed methodology uses geographic information system and geographically weighted Poisson regression (GWPR). Five variables are positively associated with pedestrian risk around schools: number of school crossing guards, land use diversity, residential density, deprivation and population density (children). GWPR permitted to demonstrate the local variations of risk factors throughout the island of Montreal. Moreover, the better knowledge of these variations can potentially help public policy makers to address local realities in more efficient interventions planning.